The Use of Data-driven Transformations and Their Applicability in Small Area Estimation - Natalia Rojas-Perilla (WISTA – Wirtschaft und Statistik, 2021)
In general, researchers have been using data transformations as a go-to tool to assist scientific work under the classical and linear mixed regression models instead of developing new theories, applying complex methods or extending software functions. However, transformations are often automatically and routinely applied without considering different aspects on their utility. This work summarizes the main findings from the paper by the author (Rojas-Perilla, 2018), which presents a unified theory of datadriven transformations for linear and linear mixed regression models that includes applications to small area prediction and the development of open source software. – – Im Allgemeinen nutzen Forscherinnen und Forscher Daten-Transformationen als Hilfsmittel für die wissenschaftliche Arbeit unter den klassischen und linearen gemischten Regressionsmodellen, anstatt neue Theorien zu entwickeln, komplexe Methoden anzuwenden oder Softwarefunktionen zu erweitern. Allerdings werden Transformationen oft automatisch und routinemäßig angewendet, ohne verschiedene Nutzenaspekte zu betrachten. Diese Arbeit fasst die wichtigsten Erkenntnisse aus der Dissertation der Autorin (Rojas-Perilla, 2018) zusammen, die eine einheitliche Theorie der datengetriebenen Transformationen für lineare und lineare gemischte Regressionsmodelle vorstellt, die Anwendungen im Bereich Small Area Estimation (SAE)-Verfahren und die Entwicklung von Open-Source-Software enthält.
Keywords: 519; Data-driven transformations; small area estimation; poverty mapping; generalized regression models; datengetriebene Transformationen; Small-Area-Schätzung; Armutsabbildung; verallgemeinerte Regressionsmodelle